Combination therapy for multidrug‐resistant cytomegalovirus disease. Issue 5 (3rd October 2015) - Stuehler, C.; Stüssi, G.; Halter, J.; Nowakowska, J.; Schibli, A.; Battegay, M.; Dirks, J.; Passweg, J.; Heim, D.; Rovo, A.; Kalberer, C.; Bucher, C.; et al.
Abstract Multidrug‐resistant (MDR) cytomegalovirus (CMV) emerged after transient responses to ganciclovir, foscarnet, and cidofovir in a CMV‐seropositive recipient who underwent allogeneic hematopoietic stem cell transplantation from a CMV‐seronegative donor. Experimental treatments using leflunomide and artesunate failed. Re‐transplantation from a CMV‐seropositive donor supported by adoptive transfer of pp65‐specific T cells and maribavir was followed by lasting suppression. This case illustrates that successful MDR CMV therapy may require individualized multidisciplinary approaches.